Paediatric adverse drug event clinic. (24th May 2012) - Beesley, OR; Thompson, JP; Powell, R; Spear, E; Tuthill, DP
Abstract : Introduction: Of paediatric admissions to hospital, up to 1.8% are a consequence of Adverse Drug Reactions (ADR); a proportion are allergic reactions. Misdiagnosis of drug allergy is important not only for the patient, but also because unevaluated reactions can lead to less effective and more expensive drugs being prescribed. Aim: To describe the suspected causative drugs, clinical features, investigations, diagnosis and advice given to patients presenting to the Paediatric Adverse Drug Event Clinic. Methods: A retrospective clinic note review was undertaken of all patients presenting to the Adverse Drug Event Clinic with a suspected drug allergy between 2005 and 2010. Children were identified though the electronic letter copies of one consultant. Results: Table 1 : 66 children (mean age 9.7 years) attended. The suspected drugs were: Antimicrobials (26), Local anaesthetics (17), General anaesthetics (16), Other (7). Rash (31), swelling (28) and urticaria (13) were the most common clinical presentations (table 1 ). Table 2 : A diagnosis of drug allergy was given in 14 children (21%); all were advised to avoid the drug. Conclusions: Medication and Anaesthetic charts are vital in the assessment of potential drug allergy. Investigation to multiple drugs is generally possible in one clinic visit. Around a quarter had a "confirmed" drug allergy. A Drug Challenge (Direct provocation test) was infrequently required to manage the children. These results are in concordance with the British Society for Allergy and Clinical Immunology guidelines, which recommends a drug challenge should only be considered after other investigations have been exhausted and the diagnosis is still unclear.